The Effect of Media Tone on Youth Trust in Government - Lee, Josephine (Advances in Social Sciences Research Journal, 2025)
Public trust in U.S. democratic institutions is at historic lows, particularly among younger generations. This study examines how narrative framing of democracy influences adolescents’ coping strategies and civic engagement intentions. Ninety-three high school students in New Jersey were randomly assigned to read pessimistic, neutral, or optimistic passages about the state of U.S. democracy and completed survey measures adapted from the COPE Inventory. Factor analysis revealed three clusters of responses: active engagement, institutional confidence, and voting intention. Results showed that neutral frames paradoxically produced the lowest confidence in democracy, while pessimistic frames heightened concern and correlated with greater willingness to engage in protest or activism. These findings extend research on framing effects (Cappella & Jamieson, 1996) and youth political psychology (Oosterhoff et al., 2018) by highlighting the role of coping mechanisms in democratic resilience. Implications suggest that civic education and political communication strategies should account for the ways adolescents transform concern into constructive participation.